Evidence-based practice in exercise science the six-step approach - Amonette, William E. 1977-; English, Kirk L. 1975-; Kraemer, William J. 1953- (Champaign, IL Human Kinetics, 2016)
"Evidence-Based Practice in Exercise Science: The Six-Step Approach equips readers with the basic skills and competencies for discerning the value of scientific research. Using a methodical approach, students and professionals will learn to identify appropriate evidence to support novel interventions and avoid counterproductive or dangerous information to eliminate ineffective exercise options. This text is an instruction manual in understanding and applying evidence-based practice. The process is divided into six steps that begin with asking a question and then finding, evaluating, implementing, confirming, and re-evaluating the evidence."--Back cover
The need for evidence-based practice in exercise science -- The process of evidence based-practice -- Philosophy, science, and evidence-based practice -- Sources of evidence -- Reading and interpreting research evidence -- Developing a question -- Searching for evidence -- Evaluating the evidence -- Incorporating evidence into practice -- Confirming the evidence -- Reevaluating the evidence -- Exercise prescription -- Exercise for special populations -- Nutrition and supplementation -- Exercise devices and apparel.
Includes bibliographical references and index.
Keywords: Sports Medicine -- Case Reports; Athletic Injuries -- prevention & control -- Case Reports; Evidence-Based Practice -- Case Reports; Exercise -- physiology -- Case Reports; Exercise Therapy -- Case Reports